Notice the counterintuitive nature

sum [ f(x) - f(x - period f) ] =/= sum [ f(x) ] - sum[ f(x - period f) =/= 0.

even if f(x) - f(x - period f) = 0 and sum [ 0 ] = 0.

I have to think more about this.

Any ideas ?

I considered using tommysum[f(x)] := continuum sum [f(x) - f(0)].

regards

tommy1729

sum [ f(x) - f(x - period f) ] =/= sum [ f(x) ] - sum[ f(x - period f) =/= 0.

even if f(x) - f(x - period f) = 0 and sum [ 0 ] = 0.

I have to think more about this.

Any ideas ?

I considered using tommysum[f(x)] := continuum sum [f(x) - f(0)].

regards

tommy1729